Problematic Fatwa: An In-Depth Sociological Investigation of MUI’s Fatwa on Supporting Palestine’s Struggle - Amin, Abd. Rauf Muhammad; Syatar, Abdul; Mayyadah, Mayyadah; Abubakar, Achmad; Haq, Islamul (El-Usrah: Jurnal Hukum Keluarga, 2024)
The purpose of this study is to assess and reveal the social background of the emergence, the suitability of methodology and istidlāl, and the problematic aspects of the Indonesian Ulema Council Fatwa Number 83 of 2023 concerning the Law of Support for the Palestinian Struggle. This research is empirical with a sociology of law approach. Data sources were obtained through MUI fatwa, interviews with a number of MUI administrators in the region, and literature study data. Data analysis through the stages of reduction, presentation, and conclusion. The research found that the social background of the fatwa arose due to questions and pressure on MUI to respond to the social reality that occurred in Palestine. In the fatwa of support for the Palestinian cause, MUI uses the naş approach and the qaulī approach. The opinions of the madhhab scholars quoted are dominated by the al-Shāfi'ī madhhab. The construct of istidlāl is in accordance with the fatwa methodology established by MUI. Meanwhile, the problematic dimension of the fatwa lies in the ruling of "haram" without explaining the criteria. Haram cannot be ruled on something that is not convincing. The reaction of intellectuals on social media, both pro and contra the fatwa, to the fatwa is an indication to question the competence and representation that MUI wants to bring. MUI did not release the list of boycotted products (at least criteria/indication), so it backfired on some of the affected products. In the future, MUI's assertiveness in issuing fatwa is still needed with language that is easier to understand.